ANALISIS FINANSIAL DISTRESS PADA RUMAH SAKIT SUMBER HIDUP GEREJA PROTESTAN MALUKU DI KOTA AMBON - Givingdelord Forrymin Cleyristel Sahureka; Steven Siaila (Soso-Q : Jurnal Manajemen, 2020)
This study aimed at determining the position of Sumber Hidup Hospital, Maluku Protestant Church according to the financial distress analysis. In this study, the hypothesis being tested was how is the position of Sumber Hidup Hospital, Maluku Protestant Church in accordance with financial distress analysis? The data used in this study were 19 months of monthly financial reports on Sumber Hidup Hospital, Maluku Protestant Church from 2019-2020. The independent variables were the liquidity ratio, leverage ratio and profitability ratio. The dependent variable in this study was financial distress. The analysis technique used was the comparative method. This study used the Altman Z-Score model to determine financial distress. The results of this study was categorized as being in financial distress for two consecutive years, namely from the year 2019 to 2020 where this condition showed the potential for bankruptcy of the company.  Keywords: Altman Score, Liquidity Ratio, Leverage Ratio, Profitability Ratio, Financial Distress